Analysis of aquaporins in Brassicaceae species reveals high-level of conservation and dynamic role against biotic and abiotic stress in canola - Sonah, Humira (Sci Rep, 2017)
Aquaporins (AQPs) are of vital importance in the cellular transport system of all living organisms. In this study, genome-wide identification, distribution, and characterization of AQPs were determined in Arabidopsis lyrata, Capsella grandiflora, C. rubella, Eutrema salsugineum, Brassica rapa, B. oleracea, and B. napus (canola). Classification and phylogeny of AQPs revealed the loss of XIPs and NIP-IIIs in all species. Characterization of distinctive AQP features showed a high level of conservation in spacing between NPA-domains, and selectivity filters. Interestingly, TIP3s were found to be highly expressed in developing seeds, suggesting their role in seed desiccation. Analysis of available RNA-seq data obtained under biotic and abiotic stresses led to the identification of AQPs involved in stress tolerance mechanisms in canola. In addition, analysis of the effect of ploidy level, and resulting gene dose effect performed with the different combinations of Brassica A and C genomes revealed that more than 70% of AQPs expression were dose-independent, thereby supporting their role in stress alleviation. This first in-depth characterization of Brassicaceae AQPs highlights transport mechanisms and related physiological processes that could be exploited in breeding programs of stress-tolerant cultivars.